2003
DOI: 10.1046/j.1471-4159.2003.01807.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine receptor CCR5 is not a necessary inflammatory mediator in kainic acid‐induced hippocampal injury: evidence for a compensatory effect by increased CCR2 and CCR3

Abstract: Chemokines and their receptors have been strongly implicated in the inflammatory process. However, their roles in excitotoxic brain injury are largely unknown. In this study we used C-C chemokine receptor 5 (CCR5) knockout (KO) mice to investigate the role of CCR5 in neurodegeneration induced by intranasal administration of the excitotoxin kainic acid (KA). Although KA treatment resulted in an increased CCR5 mRNA level in the hippocampi of wild-type mice, a CCR5 deficiency in KO mice did not affect either the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The CXCR2 knockout approach could induce a compensatory regulation of other chemokines or chemokine receptors. 32,33 This collateral effect was not clearly observed in our short-term pharmacological inhibition model. Importantly, Chen et al showed that the role of CCR5 in excitotoxic injury in CCR5 knockout mice was compensated by increased CCR2 and CCR3 expression.…”
Section: Montecucco Et Al Evasin-3 Reduces Myocardial Reperfusion Injurymentioning
confidence: 61%
See 1 more Smart Citation
“…The CXCR2 knockout approach could induce a compensatory regulation of other chemokines or chemokine receptors. 32,33 This collateral effect was not clearly observed in our short-term pharmacological inhibition model. Importantly, Chen et al showed that the role of CCR5 in excitotoxic injury in CCR5 knockout mice was compensated by increased CCR2 and CCR3 expression.…”
Section: Montecucco Et Al Evasin-3 Reduces Myocardial Reperfusion Injurymentioning
confidence: 61%
“…Importantly, Chen et al showed that the role of CCR5 in excitotoxic injury in CCR5 knockout mice was compensated by increased CCR2 and CCR3 expression. 33 On the other hand, a compensatory upregulation of CCL2 and CCL4 was recently showed in myocardial reperfusion injury in CCR5 and apolipoprotein E double knockout mice. 14 Furthermore, Evasin-3 selectively binds CXCL2 and CXCL1 but not other CXCR2 ligands (such as macrophage migration inhibitory factor) that could be released during reperfusion in the in vivo I/R model.…”
Section: Montecucco Et Al Evasin-3 Reduces Myocardial Reperfusion Injurymentioning
confidence: 99%
“…Our data differ somewhat from results obtained in CCR5-knockout mice, therefore suggesting that congenital and acquired deficiencies in CCR5 may lead to different phenotypes. In congenitally CCR5-deficient animals, KA-induced seizure activity was little different from that seen in controls, in which an increased CCR5 mRNA level was observed (101). KA was administered intranasally in those studies, while we injected it i.p.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to this, recent evidence suggests that IL-16 may play a neuroprotective role by interacting with its binding partner, CD4 and its co-receptor CCR5 as these have been shown to be expressed in several cell types within the CNS (Omri et al, 1994, Sorce et al, 2011. Indeed, CCR5 has been shown to be upregulated by a number of neurotoxic insults including kainic acid (Chen et al, 2003). Furthermore, motor neuron death is accelerated in the absence of CCR5 (Gamo et al, 2008) and CCR5 deficient mice have reduced infarct size indicating a protective role of this receptor (Sorce et al, 2010) but whether this is mediated via glia cells or a direct action on neurons is unknown.…”
Section: Lymphocyte-mediated Neuroprotection Is Contact-independentmentioning
confidence: 98%